Single Stage Nasal Reconstruction in a Near Total Nasal Defect - Vimalendu Brajesh; Aditya Aggarwal; Sukhdeep Singh; Vishal Vora; Kanika Rana (Indian Journal of Plastic Surgery)
Reconstruction of nasal defect is difficult and challenging. A full-thickness defect of nose requires reconstruction of thin inner lining, middle skeletal (bony/cartilaginous) support, and outer skin layer cover. Large full-thickness defects of nose require complex multistage reconstruction to achieve good functional and aesthetic result. We present here a case of 12-year-old boy, a known case of xeroderma pigmentosa, who underwent wide local excision for squamous cell carcinoma of the nose, leaving a near total defect of the external nose. The reconstruction was done with a suprafascial, thin radial artery forearm free-flap for the external cover as well as the inner lining along with the septal cartilage graft for skeletal support in a single stage.